Using Magnetic Levitation to Separate Mixtures of Crystal Polymorphs1. Issue 39 (12th August 2013) - Atkinson, Manza B. J.; Bwambok, David K.; Chen, Jie; Chopade, Prashant D.; Thuo, Martin M.; Mace, Charles R.; Mirica, Katherine A.; Kumar, Ashok A.; Myerson, Allan S.; Whitesides, George M.
<x xml:space="preserve">Abstract</x> Magnetic levitation (MagLev) provides a simple method for the separation of crystal polymorphs that differ in density (Δρ) by greater than 0.001 g cm−3. Density‐based separations of multiple crystalline forms were shown for four organic compounds: 5‐methyl‐2‐[(2‐nitro‐ phenyl)amino]‐3‐thiophenecarbonitrile, sulfathiazole, carbamazepine, and trans‐ cinnamic acid.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>